Relevansi Penggunaan Metode Ceramah pada Pembelajaran Abad 21 melalui Analisis Hubungan Tanggapan Peserta didik dengan Hasil Belajar Kognitif - Sari, Nurpita; Wulandari, Dyah; Jamil, Nuraisah (International Conference on Islamic Studies, 2022)
The development of science and technology leads students to learn independently by utilizing technology. 21st century learning is carried out by adapting to the learning styles of millennial generation children who use audio-visual formats more, rely on technology and like learning with teachers who position themselves as friends. However, based on the results of observations, the learning carried out at SMK Bina Budi still uses the lecture method. However, the lecture method still has many advantages, which is mentioned by Tarmudji that by using the lecture method educators can summarize learning material so that it is easy for students to understand and educators can more easily master class conditions, students are also trained to use their sense of hearing well, trained to be able to conclude material quickly and precisely. The method used in this research is quantitative correlation of two variables, the sampling technique in this study uses saturated sampling. The data analysis techniques used are validity test, reliability test, normality test, homogeneity test, linearity test, correlation test and significant t test. Based on the results of data analysis, it was concluded that the students' responses to the lecture method had a significant relationship to the students' cognitive learning outcomes. This shows that the use of the lecture method is still relevant for use in the learning process. The method used in this research is quantitative correlation of two variables, the sampling technique in this study uses saturated sampling. The data analysis techniques used are normality test, homogeneity test, linearity test, correlation test and significant t test. Based on the results of data analysis, it was concluded that the students' responses to the lecture method had a significant relationship to the students' cognitive learning outcomes. This shows that the use of the lecture method is still relevant for use in the learning process.